Exhausted T cells in systemic lupus erythematosus patients in long‐standing remission. (28th February 2021) - Lima, G.; Treviño‐Tello, F.; Atisha‐Fregoso, Y.; Llorente, L.; Fragoso‐Loyo, H.; Jakez‐Ocampo, J.
Summary: The mechanisms that drive systemic lupus erythematosus (SLE) patients to achieve remission are unknown; one possible explanation might be T cell exhaustion. The aim of the present study was to measure CD4 + and CD8 + T cell exhaustion in SLE patients in prolonged remission (PR‐SLE) and compared them with patients with active SLE (Act‐SLE) and healthy subjects. We included 15 PR‐SLE patients, 15 Act‐SLE and 29 healthy subjects. T cell exhaustion was determined by flow cytometry according to the expression of programmed cell death 1 (PD)‐1, T cell immunoglobulin and mucin 3 (Tim‐3), natural killer cell receptor (2B4), eomesodermin (EOMES) and T‐box transcription factor TBX21 (T‐bet) in CD4 + and CD8 + T cells. Dimensionality reduction using the T‐distributed stochastic neighbor‐embedding algorithm and clustering analysis was used for the identification of relevant populations. Percentages of CD3 +, CD4 + and CD8 + T cells were similar among groups. We identified five subpopulations of CD8 + and seven of CD4 + cells. The CD4 + T‐bet + CD45RO + cells identified in the unsupervised analysis were significantly increased in PR‐SLE versus Act‐SLE [median = 0·20, interquartile range (IQR) = 1·74–30·50 versus 1·68, IQR = 0·4–2·83; P  < 0·01]. CD4 + EOMES + cells were also increased in PR‐SLE versus Act‐SLE (5·24, IQR = 3·38–14·70 versus 1·39, IQR = 0·48–2·87; P  < 0·001). CD8 + EOMES + cells were increased in PR‐SLE versus Act‐SLE (37·6, IQR = 24·9–53·2 versus 8·13, IQR = 2·33–20·5; P  < 0·001). Exhausted and activated T cells presented an increased frequency of PD‐1, CD57 and EOMES in SLE patients versus healthy subjects. Some subpopulations of T cells expressing markers associated with exhaustion are increased in patients in remission, supporting T cell exhaustion as a tolerance mechanism in SLE. Exhaustion of specific populations of T cells might represent a potential therapeutic tool that will contribute to the goal of achieving sustained remission in these patients. Abstract : T cells expressing markers associated with exhaustion are increased in patients in remission, supporting T cell exhaustion as a tolerance mechanism in SLE.